Biography of Willem Iskandar and his role in education In North Sumatra: Biografi Willem Iskandar Dan Perannya Dalam Pendidikan Di Sumatera Utara - Syarifah; Desinora Natalia Hutauruk; Diancrisy Situmeang; Maria Innest; Siti Nurhidayah Al-Anshari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study is to know the biography of educational figure willem iskandar, and the role of willem iskandar in education in north sumatra.The method used in this study is library research..Data collection techniques carried out in this study are to analyze and explore several journals, books as well as sources of data or information that are considered relevant to research.From the results of research conducted that an educational figure before ki hajar dewantara founded the school in 1922, willem iskandar has founded a teacher school in tano bato mandailing natal north sumatra in 1862 while also being a teacher in the school.Other than being a teacher, willem iskandar is also a translator and author whose works inspire the community especially in mandailing.Various challenges faced willem iskandar in establishing teacher school, with his hard work in the with hard work in teach and educate teachers can produce some students who perform as a teacher, author and there are as a teacher and author.